Density functional theory study of active sites on nitrogen-doped graphene for oxygen reduction reaction. Issue 9 (1st September 2021) - Yan, Ping; Shu, Song; Zou, Longhua; Liu, Yongjun; Li, Jianjun; Wei, Fusheng
Abstract : Oxygen reduction reaction (ORR) remains challenging due to its complexity and slow kinetics. In particular, Pt-based catalysts which possess outstanding ORR activity are limited in application with high cost and ease of poisoning. In recent years, nitrogen-doped graphene has been widely studied as a potential ORR catalyst for replacing Pt. However, the vague understanding of the reaction mechanism and active sites limits the potential ORR activity of nitrogen-doped graphene materials. Herein, density functional theory is used to study the reaction mechanism and active sites of nitrogen-doped graphene for ORR at the atomic level, focusing on explaining the important role of nitrogen species on ORR. The results reveal that graphitic N (GrN) doping is beneficial to improve the ORR performance of graphene, and dual-GrN-doped graphene can demonstrate the highest catalytic properties with the lowest barriers of ORR. These results provide a theoretical guide for designing catalysts with ideal ORR property, which puts forward a new approach to conceive brilliant catalysts related to energy conversion and environmental catalysis.